Do pregnant women living in higher well-being populations in the USA experience lower risk of preterm delivery? A cross-sectional study - Jeph Herrin; Harlan M Krumholz; Carley Riley; Brita Roy; Erica Spatz; Mark T Silvestri; Anita Arora; Kenneth P Kell; Elizabeth Y Rula (BMJ Open)
Objective To determine if preterm birth, defined as gestational age <37 weeks, is lower for women living in counties with higher well-being, after accounting for known individual risk factors.Design Cross-sectional study of all US births in 2011.Participants We obtained birth data from the National Center for Health Statistics which included 3 938 985 individuals.Main outcomes measures Primary outcome measure was maternal risk of preterm delivery by county; primary independent variable was county-level well-being as measured by the Gallup-Sharecare Well-Being Index (WBI).Results Women living in counties with higher population well-being had a lower rate of preterm delivery. The rate of preterm birth in counties in the lowest WBI quintile was 13.1%, while the rate of preterm birth in counties in the highest WBI quintile was 10.9%. In the model adjusted for maternal risk factors (age, race, Hispanic ethnicity, smoking status, timing of initiation of prenatal visits, multiparity, maternal insurance payer), the association was slightly attenuated with an absolute difference of 1.9% (95% CI 1.7% to 2.1%; p<0.001).Conclusions Pregnant women who live in areas with higher population well-being have lower risk of preterm birth, even after accounting for individual risk factors.